The role of policies in supporting biodegradable medical innovations for sustainable healthcare systems: A research review - Karenza, Rachel Lusy (EcoVision: Journal of Environmental Solutions, 2026)
Background: The global health crisis is a complex issue that requires coordinated efforts among individuals, organizations, and institutions. In this context, health policies play a crucial role in improving quality of life and population well-being. With the growing development of medical innovations based on biodegradable materials particularly in the advancement of medical devices and technologies strong policy support is essential. Such policies are expected to promote the adoption of sustainable innovations through the use of biodegradable materials, which not only have the potential to enhance healthcare effectiveness but also to support the long-term sustainability of health systems in the future. Methods: This study employs a literature review method to examine the role of policy in supporting medical innovation based on biodegradable materials for healthcare system sustainability. Secondary data were obtained from peer-reviewed journal articles published between 2020 and 2025 and indexed in Google Scholar. Findings: This study demonstrates that public policy plays a strategic role in accelerating medical innovation based on biodegradable materials to achieve a sustainable healthcare system. Through research support, regulation, and funding in various countries such as the European Union, the United States, China, and Japan, the development of eco-friendly biomaterials such as PLA, PCL, and magnesium composites has been promoted to reduce environmental impacts while enhancing the efficiency and resilience of the healthcare sector. Conclusion: The synergy between public policy and biomedical innovation using biodegradable materials is essential for creating a sustainable and resilient healthcare system. Government support and sustainability-oriented policies foster energy efficiency, renewable energy adoption, and effective waste management worldwide. Novelty/Originality of this article: This study emphasizes that integrating public policy with biodegradable-based medical innovation is vital for building a sustainable healthcare system. By combining policy, biomedical engineering, and environmental perspectives, it offers a more comprehensive approach than previous studies. The findings show that strong policy–innovation synergy can lay the groundwork for future sustainable healthcare development.